Theoretical calculation of n+235U reaction. (August 2021) - Guo, Hairui; Chen, Wendi; Ye, Tao; Sun, Weili; Han, Yinlu; Cai, Chonghai
Highlights: The n+ 235 U reaction is consistently calculated and analyzed at E n ⩽ 150 MeV. Reasonable energy spectra and DDXs of light particle emissions are provided. The present results are in good agreement with the experimental data generally. Abstract: The design of Generation-IV nuclear reactors and the studies of advanced fuel cycles require high-precision nuclear data in the fast neutron energy region, one of the most important of which is n+ 235 U reaction data. The cross sections, angular distributions, energy spectra and double differential cross sections of neutron, proton, deuteron, triton, 3 He and α particle emissions and the γ production cross section and spectrum from n+ 235 U reaction are analyzed by using theoretical nuclear models in the energy range of E n ⩽ 150 MeV. The calculated results are compared with recent experimental data and the evaluated data from ENDF/B-VIII.0 and JENDL-4.0.